Stability and Oxidation Products of Hydrolysable Tannins in Basic Conditions Detected by HPLC/DAD–ESI/QTOF/MS. Issue 5 (24th June 2013) - Tuominen, Anu; Sundman, Terhi; de, Victor; Comte, Gilles; Santos‐Buelga, Celestino
ABSTRACT Introduction Hydrolysable tannins occur in plants that are used for food or medicine by humans or herbivores. Basic conditions can alter the structures of tannins, that is, the oxidation of phenolic groups can lead to the formation of toxic quinones. Previously, these labile quinones and other oxidation products have been studied with colorimetric or electron paramagnetic resonance methods, which give limited information about products. Objective To study the stability and oxidation products of hydrolysable tannins in basic conditions using HPLC with a diode‐array detector (DAD) combined with electrospray ionisation (ESI) and quadrupole time‐of‐flight (QTOF) MS. Methods Three galloyl glucoses, four galloyl derivatives with different polyols and three ellagitannins were purified from plants. The incubation reactions of tannins were monitored by HPLC/DAD at five pH values and in reduced oxygen conditions. Reaction products were identified based on UV spectra and mass spectral fragmentation obtained with the high‐resolution HPLC/DAD–ESI/QTOF/MS. The use of a base‐resistant HPLC column enabled injections without the sample pre‐treatment and thus detection of short‐lived products. Results Hydrolysable tannins were unstable in basic conditions and half‐lives were mostly less than 10 min at pH 10. Degradation rates were faster at pH 11 but slower at milder pH. The HPLC analyses revealed that various products were formed and identified to be the result of hydrolysis, deprotonation and oxidation. Interestingly, the main hydrolysis product was ellagic acid; it was also formed from galloyl glucoses that do not contain oxidatively coupled galloyl groups in their initial structures. Conclusion HPLD/DAD–ESI/QTOF/MS was an efficient method for the identification of polyphenol oxidation products and showed how different pH conditions determine the fate of hydrolysable tannins. Copyright © 2013 John Wiley & Sons, Ltd.